Clinical correlation between Anti-CCP antibody, rheumatoid factor and clinical parameters of patients with rheumatoid arthritis - Vaidya, B; Nakarmi, S; Rajbhandari, N; Bataju, P (Journal of Universal College of Medical Sciences, 2014)
BACKGROUND: The main clinically useful serological markers in patients with Rheumatoid Arthritis are Rheumatoid Factor and Anti-citrullinated Protein Antibodies (ACPA) for both diagnosis and prediction of functional and radiographic outcomes. We do not have data from Nepalese patients about gender differences and association of these antibodies with disease nature. OBJECTIVE: To identify the difference in nature of disease in relation to ACPA and gender. METHODS: A cross sectional open labeled study including consecutive patients who were diagnosed as RA according to ACR/EULAR 2010 attending the rheumatology OPD from October 2010 to October 2012 at Alka Hospital, Nepal. Data collection was done by direct patient interview and all data were recorded electronically in a predesigned performa. ACPA and RF were tested in the serum samples of 184 patients. RESULTS: Out of 184 patients, 114 of them were ACPA positive and 54 were Rheumatoid factor positive. The median duration of symptoms was 30.3±7.0 months lesser in ACPA positive patients as compared to negative ones. Mean age of females was 10.7 years less than male patients. No other significant differences were noted between male and female patients. Also, 52.3%ofRF negative patients were found to have ACPA positivity. CONCLUSION: Anti cyclic citrullinated peptide antibodies are excellent serological markers of rheumatoid arthritis, which shows good diagnostic value. This can increase the diagnostic value in addition to rheumatoid factor and its use in clinical practice may contribute to increased ability of rheumatologists to make judicious treatment decisions. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9566 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 13-16